Compressive Syndrome of the Ostio-fibrous Tunnel at Carp Level - A literary review (International Seven Journal of Health Research, 2024)
CTS tunnel syndrome is characterized by compression of the median nerve inside the carpal tunnel, at the level of the wrist. This disease still has unknown etiology, but it presents itself in a secondary way when related to other pathologies. Compression of the median nerve in the carpal tunnel occurs in most cases of nonspecific chronic flexor tenosynovitis, and it can also occur in many other nosological entities or lesions that occupy space in the tunnel. The prevalence of ostiofibrous tunnel compression syndrome at the carpal level is estimated to be between 4% and 5% of the population, ranging from 51 to 125:100,000, and it occurs more frequently in females, especially between 40 and 60 years of age. The main clinical manifestations include paresthesia in the territory of median nerve sensitivity (particularly in the thumb, index, middle and radial aspect of the ring finger), hyperesthesia (less frequent hypo or anesthesia), wrist pain that may radiate to the fingers, hands, elbows, and in some cases, even the shoulder (such symptoms may disappear with movement of the limb or massage). Diagnosis must be clinical, based on the patient's history and physical examination. For the physical examination, the Tinel and Phalen tests can be used. Complementary tests are used to make a diagnosis, the most recommended being: electroneuromyography (ENMG), magnetic resonance imaging (MRI), computed tomography (CT) and ultrasonography (US). Treatment can be conservative or surgical. The conservative way consists of adopting techniques to alleviate symptoms, such as pain control through wrist orthoses for immobilization, injections and medication, alternative therapies and physiotherapy. Surgical treatment aims to decompress the median nerve and reduce pressure on the carpal tunnel. This approach is adopted when conservative treatment does not lead to an improvement in the clinical condition within 6 to 8 weeks. This paper aims to review the medical aspects of ostiofibrous tunnel compression syndrome at the level of the carpus. The methodology used is analytical in nature through a literature review. The data extracted in the research were from the US National Library of Medicine (PubMed) with the descriptors: median nerve, wrist and carpal tunnel syndrome, according to the Health Sciences Descriptors (DeCS). To perform the crossing of these, the Boolean operator AND was used. 43 articles were found and after inclusion and exclusion criteria, 36 articles were used. Those used for inclusion: articles in English, Portuguese or Spanish, between June 2015 and July 2021, and that were available in full and for free online access. Studies that did not address the relevant concept for achieving the objective were excluded; repeated studies; according to criteria of methodological quality. Thus, the medical evaluation must be performed in a specific way, making it essential to collect the clinical history, physical exams and complementary exams in order to choose to improve conservative therapy and, later, surgical, if necessary. These facts will allow a greater therapeutic success, allowing the greatest well-being to the patient.